Estado, normas e padrões na governamentalidade neoliberal do sistema agroalimentar: a atuação do Estado e dos sistemas privados de certificação na fruticultura irrigada do Vale do São Francisco - REIS, Cinthia Regina Nunes (2017)
The main objective of this thesis is to analyze how the state has supported the promotion of a development model focused on agricultural exports, implemented on the Submedium São Francisco Valley, to understand its actions in the context of the private certification context. For this, I recurred to the theme of State action on this development model, from the perspective of the neoliberal governmentality approach, of the public policy analysis, through the State’s tools of action. As considering neoliberal governmentality as a specific way of exerting power, expressed in the art of governing from a distance, it became necessary to look to public policy as the set of State actions, focusing on the tool used on state action. So, I sought to identify the public and private actors involved on the construction and development of the region and how they relate to themselves, as well as identify the public policies by means of which the State has been supporting the agriculture on the São Francisco Valley, identifying the tools of public action, searching for transformations in the state action for maintaining the model. With this, it was possible to observe that the public and private actors have a strict relationship based on personal links, configuring itself as a permeability relationship by mean of which the State responds to the interests of the fruit producers of the region, working together with them. It was identified that the State on the federal level made itself present, in a centralized manner most of all by means of the Companhia de Desenvolvimento dos Vales do São Francisco e Parnaíba (CODEVASF), a public company created with the responsibility to implement and govern all the infrastructure on which the agricultural business was developed; besides that, it was observed that the State itself drafted, from the year 1980, attempts to reduce its direct acting on the process of maintaining the agricultural export model, that started a dialog with rules and standards defined by each consumer market, expressed in their certification systems. However, the private sector claimed and continues to demand the effective support of public action, both in the federal level as in the state and city level, to maintain the capitalistic accumulation process. In response, the State proceeds adopting economic and social policies that, direct or indirectly, seek to support the producers, guaranteeing financial investments in the maintenance of the irrigation infrastructure and on the supply of labor on the region, as well as creating structures to allow the fruit producers to reach the standards of quality imposed by their consumer markets. This way, the private certification systems have controlled not only the production process and the quality of the produce, but some state actions as well. Thus, the State remains as an important actor to maintain the development model adopted in the region, through a dialog with private interests, currently conducted from far away by the certification systems.